Biodegradable Polymers as a Noncoding miRNA Nanocarrier for Multiple Targeting Therapy of Human Hepatocellular Carcinoma. Issue 8 (4th March 2019) - Yang, Chengbin; Yin, Mingjie; Xu, Gaixia; Lin, Wei‐Jen; Chen, Jiajie; Zhang, Yinling; Feng, Tao; Huang, Peng; Chen, Chih‐Kuang; Yong, Ken‐Tye
Abstract: Therapeutic strategy based on the restoration of tumor suppressor‐microRNAs (miRNAs) is a promising approach for cancer therapy, but the low delivery efficiency of miRNA remains a huge hurdle due to the lack of safe and efficient nonviral carriers. In this work, with the use of newly developed PEGylated biodegradable charged polyester‐based vectors (PEG‐BCPVs) as the carrier, the miR26a and miR122 codelivering therapeutic strategy (PEG‐BCPVs/miR26a/miR122 as the delivery formulation) is successfully developed for efficient treatment of human hepatocellular carcinoma (HCC). In vitro study results show that PEG‐BCPVs are capable of effectively facilitating miRNA cellular uptake via a cell endocytosis pathway. Consequently, the restoration of miR26a and miR122 remarkably inhibit the cell growth, migration, invasion, colony formation, and induced apoptosis of HepG2 cells. More importantly, the chemosensitivity of HepG2 to anticancer drug is also considerably enhanced. After treatment with the PEG‐BCPV‐based miRNA delivery system, the expression of the multiple targeted genes corresponding to miR26a and miR122 in HepG2 cells is greatly downregulated. Accordingly, the newly developed miRNA restoration therapeutic strategy via biodegradable PEG‐BCPVs as the carrier should be a promising modality for combating HCC. Abstract : PEGylated biodegradable charged polyester‐based vectors (PEG‐BCPVs) can effectively encapsulate miRNAs to form the capsule‐like structure nanocomplexes by self‐assembly. In vitro study results show that PEG‐BCPVs are capable of effectively facilitating miRNA cellular uptake via a cell endocytosis pathway. Consequently, the restoration of miR26a and miR122 remarkably inhibit the cell growth, migration, invasion, colony formation, and induced apoptosis of HepG2 cells.